2019
DOI: 10.3177/jnsv.65.s122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continuous Dewaxed Brown Rice Ingestion on the Cognitive Function of Elderly Individuals

Abstract: Dewaxed brown rice (DBR), which is prepared by removing only the outermost wax layer of brown rice using a new rice milling technique, has improved water absorbency, digestibility, and taste compared to regular brown rice. DBR has a nutritional value close to that of brown rice, including a rich amount of lipopolysaccharides that are known to improve cognitive function in mice. This study thus aimed to verify the influence of continuous DBR ingestion on cognitive function among elderly individuals. The present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…Some key foods of the Mediterranean diet, such as EVOO, but also other plant-based foods including brown rice, matcha green tea and avocado, have also shown significant improvements in different cognitive domains such as speed of execution [34], orientation and language [34,35], and attention and global cognition [33][34][35]. Surprisingly, the Walnuts and Healthy Aging study, conducted at two centers, found no consistent effect of walnut consumption on global cognition in all participants.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some key foods of the Mediterranean diet, such as EVOO, but also other plant-based foods including brown rice, matcha green tea and avocado, have also shown significant improvements in different cognitive domains such as speed of execution [34], orientation and language [34,35], and attention and global cognition [33][34][35]. Surprisingly, the Walnuts and Healthy Aging study, conducted at two centers, found no consistent effect of walnut consumption on global cognition in all participants.…”
Section: Discussionmentioning
confidence: 98%
“…In a longer trial conducted over 52 older adults, consumption of 100 g/d of ultra-high hydrostatic pressurized brown rice for 2 years reduced overall cognitive decline compared to white rice intake [34]. Similarly, a crossover study of 31 older adults showed a reduction in overall cognitive decline after consuming 3 servings/d of dewaxed brown rice for 6 months [35]. In contrast, an acute crossover study comparing the consumption of rye-based bread with white wheat flour bread for 3 days did not find any effect neither in working memory nor in attention [36].…”
Section: Food-based Interventions (N = 7)mentioning
confidence: 97%
“…However, the authors noted that an even greater benefit was seen at the moderate intake level of the third quartile (OR 0.65; 95% CI 0.54, 0.78), suggesting a positive effect of rice consumption within a certain range [ 47 ]. Furthermore, a crossover trial in Japan reported lower cognition scores in 31 older adults after consuming white rice 3 times a day for 6 months compared to consuming the same amount of brown rice [ 48 ]. In the current study, brown rice was not included in the FFQ for the collection of dietary data from the participants, as white rice is more common among the Qatari population [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“… Mental health: Japanese version of Starktein’s Apathy Scale and Zung Self-Rating Depression Scale (SDS). Cognition: HDS-R score, MMSE score, FAB score, CADi score, FAB scores on “conceptualization,” and CADi scores on “time required” (s) Mental health: apathy score, SDS score, apathy scores Cognition: HDS-R score: 0; MMSE score: 0; FAB score: 0; CADi score: 0; FAB scores: ++; and CADi scores: −− Mental health: apathy score: −−; SDS score: −−; and apathy scores: −− Uenobe, 2019 2 [ 30 ] Japan 31 Crossover 84.1 [NR] 22.6 100% Japanese 100% healthy 3 meals/d of dewaxed brown rice 3 meals/d of white rice 12 mo (Period I and II: 6 mo each) HDS-R HDS-R score among those in group A, group B, group A + B, and the low cognitive function group 3 HDS-R score: group A: 0; group B: 0; group A + B: 0; and low cognitive function group: ++ Mood, anxiety, and depression Esmaeilpour, 2019 [ 40 ] Iran 100 Parallel 31 [ [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] ...…”
Section: Methodsmentioning
confidence: 99%